Study guides

☆☆

Q: Simplify 6a plus 9 over 12?

Write your answer...

Submit

Still have questions?

Related questions

2a² + 6a

12a- 6a + a = 7a Since they all have the same variable, you can simply add and subtract 12-6 = 6 6+1 = 7

11a+7b-(3b-2a)

21a - 6a

Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?

a+6a+a=8a

(a^2+7a-8)/(a^2+6a-7) (original equation) (a+8)(a-1)/(a+7)(a-1) (simplify top and bottom) (a+8)/(a+7) <--answer

6a

6a^2 - 6ab + 7a^2 = 13a^2 - 6ab = a * (13a - 6b)

6

Divide by 6a: 6a(a + 3b)

12a2/(2ab) = 6a/b

54qba

98a + 5 + 6a = 104a + 5

12a2b + 6a = 6a(2ab + 1)

6ax2 + 6ax + 6a = 6a(x2 + x + 1)

(2a - 3)(3a - 4)

It is 6a + 12, an expression which cannot be evaluated without the value of a.

Add them together: 3a+4a-a = 6a

-6a + 8 = 2 -6a = -6 a = 1

18

the answer is 6a

6a - 8 - 4a - 2 → 6a - 4a - 8 - 2 → 2a - 10

It is: (2a+3)(3a+4) when factored

-4 + 10 + 6a - 2a + 3 9 + 4a